Addisonian crisis complicated by rhabdomyolysis and acute kidney injury - Tahir, Hassan; Nagadarshini, Nagadarshini Ramagiri; Ullah, Saad; Ahmed, Arslan (International Journal of Research in Medical Sciences, 2017)
Addisonian Crisis is an endocrine emergency requiring hospitalization and urgent management. The diagnosis is usually complicated by nonspecific sign and symptoms of primary adrenal insufficiency. A high degree of suspicion Is required in such cases. Rhabdomyolysis caused by addisonian crisis is a rare complication which was seen in our patient.